Field Experiment on Soaking Characteristics of Collapsible Loess - Zhichao Wang; Yongli Xie; Junling Qiu; Yuwei Zhang; Haobo Fan (Advances in Materials Science and Engineering)
In collapsible loess area, migration of soil moisture often causes the temporal discontinuity and spatial nonuniformity of collapsibility, which leads to great damage for infrastructures. Therefore, the research on water infiltration is the key to solving the problem of collapsibility. The aim of this paper is to investigate the spatiotemporal evolution of infiltration characteristics of collapsible loess. A field soaking experiment was conducted on collapsible loess in western China, in which a soaking pool with diameter of 15 m was built. Time-Domain-Reflectometry (TDR) system and soil sampling were employed to measure the water content within the depth of 12 m. Then the saturation isograms were drawn for visualization of the process of infiltration. Also, a pilot tunnel was excavated to investigate how the free face can affect the infiltration behaviors. The experimental results revealed the characteristics of infiltration in both horizontal and vertical directions. Moreover, the response of free face on infiltration behaviors was also found. These findings of research could provide the data for the infiltration laws of unsaturated loess and thereby provide the basis for integrated treatment of collapsible loess.